Green tribology : emerging technologies and applications - Rao, T. V. V. L. N. (CRC Press, 2022)
"Green tribology includes focus on innovative surfaces, lubricants, and materials to reduce friction and wear for environmental conservation and sustainability. This book creates a platform for sharing knowledge emerging in the field of green tribology and focuses on advances and developments in technologies and applications. Aimed at advanced students, researchers, and industry professionals, this book will be of interest to readers seeking to understand and apply sustainable practices in tribology and lubrication engineering and related fields"-- Provided by publisher.
Keywords: Tribology -- Environmental aspects.; elektronické knihy; electronic books